Malaysian Carica papaya L. var. Eksotika: Current Research Strategies Fronting Challenges - Sekeli, Rogayah; Hamid, Muhammad Hanam; Razak, Roslinda A.; Wee, Chien-Yeong; Ong-Abdullah, Janna (Frontiers in Plant Science, 2018)
Carica papaya L. or commonly known as papaya, is a major tropical crop consumed worldwide either as a vegetable or fresh fruit or processed products. In Malaysia, papaya was initially planted as a smallholder crop throughout the country. Eventually after 15 years of breeding and selection, a new variety, named Carica papaya L. var Eksotika, was released by the Malaysian Agricultural Research and Development Institute (MARDI) in 1987. This event changed the outlook of papaya planting from a smallholder crop to a plantation crop. Despite the blooming papaya business, the industry faced various disease issues that jeopardize its future. The most devastating was the papaya dieback disease, which affected approximately 800 hectares of plantation, destroyed approximately 1 million trees nationwide with total losses estimated at US 58 million. Even though Eksotika is a favored commercial variety with good eating and aesthetic quality fruit, its potential for more lucrative distant markets is tarnished with its short-shelf life fruits. Several strategies had been reported to address the challenges faced by Eksotika specifically against the dieback disease and the fruit’s short shelf-life. This review focuses on Carica papaya L. var Eksotika particularly on the strategies to address the challenges faced in order to sustain the economic value of this crop plant, which had contributed significantly to the Malaysian economy.